Application of the Global Warming Learning System (GWLS) as an Effort to Improve Student’s Learning Outcomes and Critical Thinking Ability - Astuti, Adina Widi; Mindyarto, Budi Naini; Aji, Mahardika Prasetya; Astuti, Budi; Atun, Cholis (Universitas Negeri Semarang, 2024)
This Classroom Action Research (CAR) aims to improve learning outcomes and critical thinking skills of class X-K SMA Negeri 6 Semarang, through the application of adaptive teaching materials Global Warming Learning System. The learning model used is Problem Based Learning with group investigation method (cycle I) and Project Based Learning with product differentiation (cycle II). CAR is carried out in two cycles, where each cycle consists of four activities, namely action planning, action implementation, observation and reflection which adopts the Kemmis and Taggart models. Data collection techniques used in this study were observation, tests, questionnaires and interviews. Data analysis used a qualitative descriptive approach based on educational outcomes and improving students' critical thinking skills. The results show that there has been an increase in educational outcomes and critical thinking skills (pre-cycle to cycle I) and (cycle I to cycle II). Evidenced by the results of studying at first cycle, which was completed by 15 students (41.67%) and the students' critical thinking skills, the average 71.59% was high category. Meanwhile the educational outcomes of physics cycle II which were completed were 28 students (77.78%) and the ability to think critically with an average 78.88% was high category